THE TOS STUDY CONTROL DATA: HOW WELL DO NEUROLOGY IN–PATIENTS RECALL BEING EXAMINED AND DOES IT MATTER?. Issue 11 (9th October 2013) - Mulla, Adam; Appleton, Jason; Nicholl, David
Abstract : Background: We have recently developed a method of assessing the quality of neurological examination: the TOS score, which involves asking patients if they recall being examined with a Tendon hammer (T), Ophthalmoscope (O) and Stethoscope (S). 1 33% of 93 patients referred to neurology in 2 hospitals could not recollect being examined with a tendon hammer and 48% said they had not been examined with an ophthalmoscope. In contrast, the majority (95.7%) remembered the use of a stethoscope in their examination. One of the limitations of the TOS study was potential recall bias, so we decided to measure TOS scores on a patient group we knew had been examined. Methods: Prospective data collection over a four month period. We asked patients on discharge who were admitted under neurology whether they recalled being examined with a tendon hammer, ophthalmoscope and stethoscope during their hospital stay by showing them a standardised poster with a doctor using these three objects. Exclusion criteria included confused patients, those unable to communicate a response and those whose in–hospital stay was longer than a week. Results: Of 45 patients discharged from a neurology ward at one hospital over a four month period with a median hospital stay of 2 days, 100% recalled being examined with a tendon hammer, 97.8% remembered being examined with an ophthalmoscope, and 86.7% recalled examination with a stethoscope. Two thirds of the patients were female with a median age of 47 years (range 17–65 years). The main diagnoses on discharge were: migraine (12 (26.7%)); stroke (9 (20%)); non–organic/functional (5 (11.1%)); transient ischaemic attack (2 (4.4%)); and demyelination (2 (4.4%)). Conclusions: Although recall bias is a potential problem for the TOS score, this control data indicates that it should not be seen as a significant issue and does not negate the findings of our previous data collection that large numbers of in–patients with neurological problems are not been appropriately examined. TOS scores provide a method of quantifying the thoroughness of neurological examination and we are at present in the process of organising a multicentre study in six countries using TOS scores to establish how widespread this problem is globally.